2011
DOI: 10.1186/1471-2296-12-66
|View full text |Cite
|
Sign up to set email alerts
|

Is the beck anxiety inventory a good tool to assess the severity of anxiety? A primary care study in The Netherlands study of depression and anxiety (NESDA)

Abstract: BackgroundAppropriate management of anxiety disorders in primary care requires clinical assessment and monitoring of the severity of the anxiety. This study focuses on the Beck Anxiety Inventory (BAI) as a severity indicator for anxiety in primary care patients with different anxiety disorders (social phobia, panic disorder with or without agoraphobia, agoraphobia or generalized anxiety disorder), depressive disorders or no disorder (controls).MethodsParticipants were 1601 primary care patients participating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 32 publications
1
83
1
3
Order By: Relevance
“…Multiple regression analyses were performed using anxiety and self-compassion as predictors of disability in the GAD sample. The BAI was used as a measure of anxiety symptoms, as previous work has demonstrated that the BAI score reflects overall anxiety symptom severity [3840]. Statistical significance was set at P = 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple regression analyses were performed using anxiety and self-compassion as predictors of disability in the GAD sample. The BAI was used as a measure of anxiety symptoms, as previous work has demonstrated that the BAI score reflects overall anxiety symptom severity [3840]. Statistical significance was set at P = 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The BAI lists 21 symptoms, and the total score ranges from 0 to 63. The BAI has good psychometric properties [33] and is suitable for assessing the severity of anxiety in primary care patients with anxiety disorders [34]. The Overall Anxiety Severity and Impairment Scale (OASIS) [35] was used as a proxy for anxiety severity at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the BAI was not originally designed to measure panic but rather anxiety in general. However, the literature shows that the scale is more closely aligned to PD than to any other anxiety disorder, with higher BAI scores in panic populations than in nonpanic anxiety populations, [38][39][40][41] while its items capture the DSM-criteria for PD best. Previous studies using DSM panic symptom criteria for statistical analysis were limited by their retrospective assessment of specific symptoms that only briefly occur during a panic attack (seconds to minutes) that may have gone largely unnoticed at the time of the attack because other symptoms were predominant.…”
Section: Depression and Anxietymentioning
confidence: 95%